The relationship between firm's size, liquidity and assets tangibility on capital structure of construction companies in Malaysia / Nurul Najlaa Nordin - Nordin, Nurul Najlaa (2016)
This research contains the determinants of construction companies in Malaysia towards capital structure. The determinants are firm’s size, liquidity and assets tangibility. This research consists of collecting data from Main Board of Bursa Malaysia from year 2010 to 2015 of construction companies’ financial statement. The financial statements of 32 companies with number of observations totaling 192 were collected as sample data. The dependent variable used is capital structure meanwhile the independent variables are firm’s size, liquidity and assets tangibility. This data using panel data method and STATA been implemented to test the results. The results from this study show that there is significant positively relation between firm’s size and current ratio to debt ratio meanwhile assets tangibility negatively significant to debt ratio. The construction companies depend more on debt financing instead of equity for business extension and development.